Determinants and outcomes of women empowerment: The case of Filipino women entrepreneurs - Sulat, Mylene M. (Animo Repository, 2023)
Empowering women brings many benefits to society, including economic development. This is why the need to achieve and sustain women empowerment and gender equality remain to be among the top local and global goals. Women entrepreneurs are considered empowered individuals. As such, this study aimed to determine the social and personal factors that influence the empowerment of women entrepreneurs and to find out if their empowerment leads them to promote gender equality within and outside their workplace. The study used the lens of entrepreneurial feminism, which describes women as change agents who use their entrepreneurial competency, resources, and feminine capital to improve women’s lives and do social good. A survey questionnaire was used to gather data from 108 married Filipino women entrepreneurs. Results showed that personal characteristics, which include educational profile and place of origin, do not have any significant difference with the empowerment of women except with the active participation in socials when they were students. Components of personal responsibility, except behavioral and emotional control, were significantly correlated with women empowerment. All sources of social support (i.e., parental emotional and moral support, spousal emotional and moral support, instrumental assistance of family, and support of mentors, colleagues and women organizations) also proved highly influential to empowerment. Lastly, the results showed there was a significant relationship between women empowerment and gender equality practices. This study concludes that women entrepreneurs, as empowered individuals, promote gender equality and enable the empowerment of other women within the workplace and the community by providing equal opportunities for career growth, fair and equal remuneration, access to resources, and mentorship.